USE OF FLUOROQUINOLONES IN HOSPITALIZED CHILDEN, PRELIMINARY REPORT OF A CHART REVIEW IN A BELGIAN UNIVERSITY CHILDREN'S HOSPITAL. Issue 1 (14th December 2015) - Meesters, Kevin; Bruyne, Pauline De; Mauel, Reiner; Walle, Johan Vande
Abstract : According to international guidelines, fluoroquinolones (FQ) should only be prescribed to children when there is no alternative antibiotic. FQ resistance is a rapidly growing problem worldwide. We hypothesize that FQ are frequently prescribed off-label in children. To confirm this hypothesis, we analyzed FQ prescriptions for hospitalized children in a Belgian university hospital. Method: We reviewed all prescriptions of FQ for children up to 17 years of age who were hospitalized at Universitair Ziekenhuis Brussel, a Belgian university children's hospital, in the period 2010–2013. Patient characteristics, indication for the FQ prescription and microbial cultures were obtained from the medical file. The study was approved by the institutional review board. Results: As we foresee to finish our data analysis by the end of April 2015, we present results of our interim analysis here. Until now, a total of 178 FQ prescriptions in 79 children were analyzed. The majority of children had major comorbidities such as childhood cancer, cystic fibrosis or inflammatory bowel disease. FQ prescription was based on a microbial culture in 15.4% of cases. Frequent indications for FQ prescription were Pseudomonas eradication in cystic fibrosis patients, long term antibiotic prophylaxis in neutropenic patients and wound infections. Prescribed daily doses and consumed daily doses varied widely, even for the same indication. Concomitant medications were common and included mainly other antibiotics, steroids and chemotherapeutics. Conclusion: FQ were used as 'reserve antibiotic, ' and so on-label, in a minority of all FQ prescriptions for hospitalized children.